UV-Visible Spectrophotometric Determination of Formalin Contamination in Tofu Circulated in Maros City - Indonesia - Seniwati, Seniwati; Qawiy, Haqi Romadhona; Aminah, Aminah; Naid, Tadjuddin (Universitas Muslim Indonesia, 2022)
Tofu is one of the healthiest foods because of its high protein content and the quality is equivalent to the quality of animal protein. Formaldehyde has a function as an antibacterial agent that can slow down the activity of bacteria in foods that contain a lot of protein, so formaldehyde reacts with proteins in food and makes food durable, but when it enters the human body, formaldehyde itself is mutagenic and carcinogenic which can trigger the growth of cancer cells. and gene defects in the body. Thus, in this study, we aim to determine the formalin contamination in tofu circulated in Maros City – Indonesia. This research was conducted from December 2014 to June 2015. The analysis of formalin contamination in tofu was conducted in qualitative and quantitative analysis. The qualitative analysis was performed using the specific reagent, and the quantitative analysis was measured by UV-Vis spectrophotometric method. The result showed that sample codes RMD1 and RMD2 with formalin contaminants because the color of the solution produced after the test was red correspond to the positive result. As for the tofu sample with sample code RMD3, the results were negative because it gave a yellow color after adding potassium permanganate reagent. In the quantitative analysis, samples were measured using a UV-Vis spectrophotometer at a wavelength of 571.5 nm. From the measurement process, the result exhibited that the samples RMD1 and RMD2 contain formalin of 5.92 and 3.34 g/gram, respectively.